Penggunaan Obat Berpotensi Hepatotoksik Pada Pasien Sirosis Hati: Suatu Telaahan - Ariesta Kirana Efmisa; Armenia Armenia; Dedy Almasdy (Journal of Pharmaceutical and Sciences, 2023)
Liver cirrhosis is a pathological liver disease characterized by the formation of scar tissue and regenerative nodules in liver cells. This condition leads to changes in the shape and size of the liver, accompanied by increased pressure in the veins and reduced blood flow in the portal vein. Liver cirrhosis is the seventh leading cause of death. Drugs are the main cause of liver damage. More than 900 drugs, toxins and herbs are reported to cause liver damage. The purpose of this review article is to summarize the results of previous studies on the use of hepatotoxic drugs in patients with liver cirrhosis. Data sources for this study were identified through searching Google Scholar, PubMed and Science Direct using the keywords "hepatotoxic drugs" and "liver cirrhosis" in articles published between 2011-2022. Finally, 10 articles were obtained and analyzed. The results of this review article show that liver cirrhosis patients are still often prescribed potentially hepatotoxic drugs. Some commonly prescribed drugs include paracetamol, omeprazol, ranitidine, ceftriaxon, ciprofloxacin, atorvasatin, metformin, and amiodarone.